Abundance of Environmental Data vs. Low Public Interest in Climate and Ocean Issues. Where Is the Missing Link? - Zielinski, Tymon; Bolzacchini, Ezio; Evans, Karen; Ferrero, Luca; Gregorczyk, Klaudia; Kijewski, Tomasz; Kotynska-Zielinska, Izabela; Mrowiec, Patrycja; Oleszczuk, Barbara; Pakszys, Paulina; Piechowska, Ewa; Piwowarczyk, Joanna; et al. (Frontiers in Marine Science, 2021)
Climate change and associated modification of the ocean is a fact, however, it seems to be the most undervalued and little understood “pandemic” challenge of this century. We live in a world where environmental data is increasingly being amassed and models are generating finer scale and increasingly dense numbers of outputs, resulting in the production of high level scientific information on climate and ocean. However, the knowledge generated is often inaccessible, incomprehensible and misunderstood by society. Given that society has access to many levels of information through various forms of media, how do we better share this knowledge, and improve understanding of how society is impacting their immediate and remote surroundings and what behavioral changes are needed for reducing those impacts? In this paper, we assess the level of environmental and ocean awareness among young learners. We argue that, despite the wide range of environmental data available and a common use of a broad range of media, this group is not aware of or interested in climate related issues. This paper highlights the challenges in bringing researchers, data managers and educators together to provide consistent, up-to-date messages that can appeal to and can be understood by modern societies. It also highlights insufficiencies in environmental school education, including those concerning the “uncertainty” concept, which is a fundamental part of any scientific process. In identifying these challenges, we propose a pathway for improving societal knowledge on climate and ocean changes that takes advantage of the technological abilities for environmental data collection, storage and processing, global and regional research, as well as good practices in ocean literacy and climate and ocean education.